Study of the cooperation relationship between the front office and housekeeping departments through communication at hotel tentrem semarang - Azzahra, Mayada Saharani; Asshofi, Izza Ulumuddin Ahmad (Surya Hijau Manfaat, 2024)
This research aims to explain the effectiveness of cooperation relationship between the Front Office and the Housekeeping Departments and to improve the communication patterns of cooperative relations between the Front Office and Housekeeping. This study uses a qualitative method with a descriptive type. Data collection techniques use observation and documentation in order to obtain accurate data regarding cooperation and communication. The observations made were conducting on the job training for 6 months in the Front Office Department Hotel Tentrem Semarang. The results obtained from this study is that there are still need improvements in communication between the front office and housekeeping departments at the Tentrem Semarang hotel. To improve cooperative relations between front office and housekeeping departments is carried out through a combination of verbal and non-verbal communication. The communication must also be reinforced with clear instruction from the department heads to ensure that operations run effectively and smoothly.